Mass Transfer in An Absorption Column (International Journal of Scientific Research in Science and Technology, 2024)
The present work aims to determine the volumetric mass transfer coefficient in the liquid phase, KLa, for the removal of acetone from air through contact with water, using an absorption tower packed with glass rings. Thirty-three experiments were conducted with varying water and air flow rates, and the acetone concentrations in the liquid outlet were measured. The method used to determine the KLa coefficient was presented by Metcalf et al. (2003), where the coefficient values are determined through dC/dt versus C graphs. An evaluation of the influence of the liquid and gas input flow rates on the absorption of acetone is also presented.
Keywords: Mass Transfer Coefficient; Absorption